THE INFLUENCES OF LANGUAGE PROFICIENCY ON ACADEMIC ADAPTATION OF CHINESE INTERNATIONAL STUDENTS STUDYING IN MALAYSIA: A SYSTEMATIC REVIEW - Wujiadai, Sun; Ahmad, Hishamuddin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The past five years witnessed a significant increase in the number of Chinese international students enrolling in Malaysian universities. For international students, adapting to the host country's educational environment is a crucial theme during their studies, and the effectiveness of their academic adaptation is key to completing their studies. The researcher found that language proficiency is commonly concluded as one of the crucial influencing factors of academic adaptation in the studies of international students. Malaysia is a multilingual and multicultural country, and its unique linguistic environment and cultural background bring different challenges to international students in their academic adaptation. This study systematically reviews the studies on the influence of language proficiency on the academic adaptation of Chinese international students studying in Malaysia from 2020 to 2025. By identifying literature gaps in publishing time, sample characteristics, topics, research methods and theories, this review aims to inspire further research and enrich future achievements in this area.